PENGEMBANGAN SISTEM E-SUPERVISION PADA INSTANSI PEMERINTAH KOTA SURABAYA - Harry Angjaya; Daniel Hary Prasetyo; Daniel Soesanto (Perpustakaan Universitas Surabaya, 2018)
Project management is the planning, organizing, directing, coordinating, and monitoring the project activities to meet project objectives in terms of schedule and budget set at the beginning of the contract. In this final dissertation, the word project specifically defined as construction projects of Surabaya city government agency. Currently Surabaya city government agency uses e-Supervision to manage those projects. E-Supervision is part of Goverment Resource Management System (GRMS) support system used to monitor the physical development of construction projects as a basis of calculation for the contractor disbursement of funds (payment). In practice though, the current e-Supervision has not been able to synchronize the data between surveyors' inputs and contractor reports, making it difficult to ensure that the payment made to contractor is done accurately and based on the real physical development of the project in the field. Other weakness from the current system is there's no limit of access for the surveyor, resulting in difficulties to maintain the accountability, privacy and security of the data in the system. No cross-check process on the surveyors' input leads to higher risk of human-error in the report. Users also have difficultes in seeing the deviation between the project plan/schedule and the realization of the project so that often the payment to the contractor is done inaccurately. To address these known weaknesses, the development of e-Supervision will be made through several new features such as notifications, user access restrictions, S curve ability and adding a new role of Supervisory Consultants. Based on trials and validation by the users, the newly developed e-Supervision makes it easier for them to perform an accurate, effective and efficient project management process for Surabaya city government agency.